SHP-2 phosphatase is required for hematopoietic cell transformation by Bcr-Abl - Chen, Jing (American Society of Hematology, 2007)
SHP-2 phosphatase forms a stable protein complex with and is heavily tyrosine-phosphorylated by the oncogenic tyrosine kinase Bcr-Abl. However, the role of SHP-2 in Bcr-Abl–mediated leukemogenesis is unclear. In the present report, we provide evidence that SHP-2 is required for hematopoietic cell transformation by Bcr-Abl. In vitro biological effects of Bcr-Abl transduction were diminished in SHP-2(Δ/Δ) hematopoietic cells, and the leukemic potential of Bcr-Abl–transduced SHP-2(Δ/Δ) cells in recipient animals was compromised. Further analyses showed that Bcr-Abl protein (p210) was degraded, and its oncogenic signaling was greatly decreased in SHP-2(Δ/Δ) cells. Treatment with proteasome inhibitors or reintroduction of SHP-2 restored p210 level in Bcr-Abl–transduced SHP-2(Δ/Δ) cells. Subsequent investigation revealed that SHP-2 interacted with heat shock protein 90, an important chaperone protein protecting p210 from proteasome-mediated degradation. The role of SHP-2 in the stability of p210 is independent of its catalytic activity. Blockade of SHP-2 expression in p210-expressing cells by antisense or small-interfering RNA approaches decreased p210 level, causing cell death. Inhibition of SHP-2 enzymatic activity by overexpression of catalytically inactive SHP-2 mutant did not destabilize p210 but enhanced serum starvation-induced apoptosis, suggesting that SHP-2 also plays an important role in downstream signaling of p210 kinase. These studies identified a novel function of SHP-2 and suggest that SHP-2 might be a useful target for controlling Bcr-Abl–positive leukemias.